Determinants of the voluntary provision of public goods: experimental Investigations - Diederich, Johannes (2013)
The private provision of public goods (PPPG) is still one of the most fascinating puzzles in economics. Underpredicted by standard economic theory but outrightly evident in empirical evidence, its presence opened doors for new methods to enter the economist's toolkit and helped birthing the nowadays more vibrant than ever field of behavioral economics. Variants of the question of what determines giving in PPPG make up, for the most part, the research questions of the five articles that constitute this dissertation. Residing on the overlap of public economics, environmental economics, and behavioral/experimental economics, it reports on two field-experimental and one lab-experimental projects, delivering results with respect to, for example, the price elasticity of giving to public goods, the willingness to pay for a voluntary one-ton emissions reduction, the pronounced effect of education on PPPG, the "pure" effect of group size in public good provision, and the effects of ambient noise and outdoor temperature on PPPG.